On nature and reindeer luck - Oskal, Nils (Rangifer, 2000)
This paper describes the reindeer Sami understanding of a worthy life expressed in qualitative distinctions centred around the term 'reindeer luck'. Reindeer luck does not in itself mean a good life but is an ingredient of a good life. Reindeer luck lasts from cradle to grave but it can change along the way. To a certain degree it is possible to influence your own reindeer luck, but you can also spoil it through actions, behaviour, words and thoughts. These are more important than means-to-end rational actions with the aim of intentionally improving reindeer luck. The paths to reindeer luck are discussed with the aim of articulating the moral ideals implied in this type of understanding. This theme is discussed in regard to what we may learn from relations to nature.